Acadian Leaders and Louisiana, 1902-1955 - McNally, Carolynn (Acadiensis, 2016)
This article explores the initial contacts between the emerging elite of the Acadian Renaissance in the Maritime Provinces and Acadian descendants in Louisiana in the first half of the 20th century. Separated since the Grand Dérangement, the two groups evolved differently in Canada and the United States, but the small group of men behind the first Acadian nationalist movement neglected these changes as they celebrated the idea of a united “grande famille acadienne” sharing a common history, kinship ties, and cultural symbols such as Longfellow’s Evangeline. Including Southern Acadians in defining this collectivity did not, however, encourage lasting political or economic partnerships.